The impact of semaglutide on liver fat assessed by serial cardiac CT scans in patients with type 2 diabetes: Results from STOP trial - Golub, Ilana S.; Manubolu, Venkat S.; Aldana-Bitar, Jairo; Dahal, Suraj; Verghese, Dhiran; Alalawi, Luay; Krishnan, Srikanth; Kianoush, Sina; Benzing, Travis; Ichikawa, Keishi; Kinninger, April; Fazlalizadeh, Hooman; et al. (Nutrition, metabolism, and cardiovascular diseases, 2025)
The prevalence of hepatic steatosis continues to increase worldwide. Hepatic steatosis is increasingly recognized as an independent risk factor for cardiovascular mortality. However, there are limited options for the treatment of fatty liver. In this study, we evaluated the effect of semaglutide on liver fat as measured by non-contrast cardiac CT scans. STOP is a randomized controlled trial that evaluated the semaglutide treatment effect on coronary atherosclerosis progression (STOP) in type 2 diabetes. We utilized unenhanced cardiac CT scans to quantify liver fat based on the CT Hounsfield attenuation method. Of the 140 subjects who were originally randomized, a total of 114 individuals qualified for this study. 59 participants were in the semaglutide group and 55 were in the placebo group, and these subjects were followed for 12 months. The secondary outcome (liver fat attenuation) was quantified using non-contrast cardiac computed tomography (CT) images at both the baseline and 12-month follow-up time points. Multivariate regression models were then used to evaluate the change in liver fat content overtime. One hundred and fourteen subjects were included in the study: 61 % male, mean age of 57.8 ± 8.1 years, and mean BMI of 32.0 ± 6.7. The average of three liver measures over 12 months showed an improvement in the semaglutide group of 1.4 ± 9.0 mean HU, versus a worsening in the placebo group of 1.9 ± 9.5 mean HU. The multivariable linear regression models (after adjusting for age, gender, BMI, hypertension, hyperlipidemia, past smoking and baseline liver attenuation) showed that average liver attenuation measures improved by 4.4 HU in the semaglutide group when compared to the placebo group (p = 0.002). This result demonstrated improvement in the liver fat content within the treatment group. In type 2 diabetes patients with hepatic steatosis, treatment with semaglutide resulted in a significant improvement in fatty liver reduction when compared to placebo. •Outlines potential mechanisms by which GLP1-RAs, specifically semaglutide, may favorably influence hepatic steatosis.•Elucidates Semaglutide's impact on liver fat measures and suggests potential treatment targets for GLP1-RAs.•Highlights secondary outcomes of the STOP, including semaglutide impact on liver fat attenuation measures and change of of liver transaminases.